Dietary quality in children and the role of the local food environment - Eimear Keane; John Cullinan; Catherine P. Perry; Patricia M. Kearney; Janas M. Harrington; Ivan J. Perry; Richard Layte (Elsevier, 2016)
Diet is a modifiable contributor to many chronic diseases including childhood obesity. The local food environment may influence children's diet but this area of research is understudied. This study explores if distance to and the number of supermarkets and convenience stores in the local area around households are associated with dietary quality in nine year olds whilst controlling for household level socio-economic factors. This is a secondary analysis of Wave 1 (2007/2008) of the Growing Up in Ireland (GUI) Child Cohort Study, a sample of 8568 nine year olds from the Republic of Ireland. Dietary intake was assessed using a short, 20-item parent reported food frequency questionnaire and was used to create a dietary quality score (DQS) whereby a higher score indicated a higher diet quality. Socio-economic status was measured using household class, household income, and maternal education. Food availability was measured as road network distance to and the number of supermarkets and convenience stores around households. Separate fixed effects regression models assessed the association between local area food availability and dietary quality, stratified by sex. The DQS ranged from −5 to 25 (mean 9.4, SD 4.2). Mean DQS was higher in those who lived furthest (distance in quintiles) from their nearest supermarket (p<0.001), and in those who lived furthest from their nearest convenience store (p<0.001). After controlling for socio-economic characteristics of the household, there was insufficient evidence to suggest that distance to the nearest supermarket or convenience store was associated with dietary quality in girls or boys. The number of supermarkets or convenience stores within 1000 m of the household was not associated with dietary quality. Food availability had a limited effect on dietary quality in this study. Issues associated with conceptualising and measuring the food environment may explain the findings of the current study. Keywords: Diet, Socio-economic status, Food environment